Atypical Macular Presentation in a FRAT Case and HANAC Syndrome, A Case Report - Ferreira, Felipe de Queiroz Tavares; de Queiroz, Marjorie Fornazier Do Nascimento [UNESP]; da Fonseca, André Luis Ayres; de Freitas, Ana Cristina Lavor Holanda; Nascimento, Maurício Abujamra (Bentham Science Publishers, 2021)
Purpose: Report an atypical Familial Retinal Arterial Tortuosity (FRAT) case associated with Hereditary Angiopathy with Nephropathy, Aneurysm and Cramps (HANAC). Methods: The authors report the case of a female patient with FRAT and HANAC, and an asymmetric ocular presentation which is unusual in Familial Retinal Arterial Tortuosity patients. Conclusion: These findings help in better understanding this rare disease. HANAC Syndrome is not a common issue; thus, it is essential to understand it to make the right diagnosis. Careful ophthalmological examination plays a key role in this process since, in the herein reported case, it could have helped to diagnose a disease capable of affecting a patient’s health, although it was an atypical ocular impairment.
Keywords: Familial retinal arteriolar tortuosity; Macular hemorrhages; Retina; Retinal vascular tortuosity; Retinal vessels; Spontaneous retinal hemorrhages